PsycEXTRA Dataset 2001
DOI: 10.1037/e382702004-001
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Leadership in a Standards-based Reform

Abstract: The spotlight of educational leadership is on instructional leadership. As pressure for improving student performance in the current standards-based accountability environment swells and test results are increasingly scrutinized, school principals are being urged to focus their efforts on the core business of schooling--teaching and learning. But what does it mean to be an instructional leader? What do principals that are instructional leaders do differently than other principals? How do they spend their time?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 5 publications
1
31
0
Order By: Relevance
“…However, the responsibility for advancing a school's instructional capacity, historically borne by principals (Hallinger 2003, Barnett andAagaard 2007) is seen by many as simply too complex and overwhelming a job for a single leader given the myriad non-instructional issues that consume school leaders' attention (Portin 2000, Supovitz and Poglinco 2001, Fink and Resnick 2002, Fullan 2002, Gronn 2002, Lambert 2002, Resnick and Glennan 2002, Copland and Boatright 2006, Barnett and Aagaard 2007, Chrispeels et al 2008). These obstacles are often even more challenging for principals in urban high schools (Portin 2000, Resnick and Glennan 2002, Copland and Boatright 2006.…”
Section: Instructional Leadershipmentioning
confidence: 98%
“…However, the responsibility for advancing a school's instructional capacity, historically borne by principals (Hallinger 2003, Barnett andAagaard 2007) is seen by many as simply too complex and overwhelming a job for a single leader given the myriad non-instructional issues that consume school leaders' attention (Portin 2000, Supovitz and Poglinco 2001, Fink and Resnick 2002, Fullan 2002, Gronn 2002, Lambert 2002, Resnick and Glennan 2002, Copland and Boatright 2006, Barnett and Aagaard 2007, Chrispeels et al 2008). These obstacles are often even more challenging for principals in urban high schools (Portin 2000, Resnick and Glennan 2002, Copland and Boatright 2006.…”
Section: Instructional Leadershipmentioning
confidence: 98%
“…Leithwood, Jantzi, Silins and Dart (1993) find that principals, who focus on developing a school vision, setting group goals, holding high expectations and providing individual support for teachers, positively influence school culture and climate. Supovitz and Poglinco (2001) find that instructional leaders organise their schools around an emphasis on instructional improvement supported by a distinct vision of instructional quality; cultivate a community of instructional practice in their schools by creating a safe and collaborative environment for teachers to engage in; and deepen their work to support instructional improvement.…”
Section: Literature On Instructional Leadershipmentioning
confidence: 98%
“…Recent research has shown that organisational restructuring alone does not increase the likelihood that groups will develop communities of instructional practice (Supovitz 2001).…”
Section: Building a Positive Learning Community Of Instructional Pracmentioning
confidence: 99%
“…These behaviors are consistent with dimensions of effective school leadership noted by others. This new style of principal is expected to be: an instructional leader who promotes high expectations for student achievement and translates these expectations into daily practice (Murphy, 1990); an organizational leader, who is a collaborative builder of relationships and structures in the process of creating a learning community focused on transformation and reform through problem solving (Marsh, 2000); a public leader who builds partnerships with other schools, parents, and the community (Sarason & Lorentz, 1998), and an evidence-based leader who engages in continuous inquiry into the performance of the organization through gathering and analyzing a variety of organizational data (Schmoker, 1999;Supovitz & Poglinco, 2001). Moreover, this new style of principal engages in reflective practice and the ongoing process of examining his or her actions by being open to criticism and change and encourages others within the organization to adopt this stance (Schon, 1983;Argyris, 1990).…”
Section: Elpap Program Descriptionmentioning
confidence: 99%